Farmers' social, communication and psychological factors towards adoption of husbandry practices and innovations in small ruminant farming - Man, Norsida; Yusuf, Munifah Siti Amira; Shin, Yee Siaw; Mohd Affandi, Nurul Athira (Human Resource Management Academic Research Society, 2024)
Malaysia aims to achieve full self-sufficiency in beef and mutton, which currently below 50%. This will be achieved by promoting innovative husbandry practices among small ruminant farmers to enhance production and productivity. Despite government initiatives, small ruminant farmers in Selangor, Malaysia, continue to rely on conventional husbandry practices, resulting in low dairy production and productivity due to lack of knowledge and skills to adopt advanced husbandry practices and innovations. Therefore, this study aims to determine the social, communication and physiological factors influencing the adoption of both husbandry practices and innovations. A total of 250 small ruminant farmers were selected as respondents through simple random sampling. Data was gathered through interviews guided by a structured questionnaire and personal observations. The findings indicate that most ranchers have a high level of perception towards social, communication, and psychological factors influencing the adoption of husbandry practices and innovations. The study recommends that the effort of government support through extension services is crucial to strengthen the small ruminant industry, enabling local production to achieve a self-sufficiency level of 50%, ensuring sufficient domestic supply and reducing dependence on fluctuating imports, thereby meeting the increasing demand for ruminant-based products. Future research could investigate the effectiveness of government-supported strategies and policies in achieving targeted self-sufficiency and their impact on small ruminant industry stability.